MULTICULTURAL UKHUWAH CONCEPT: The Study of Various Signification on Ukhuwah Perspective of Islamic Elite Religion in Pasuruan District - Makhfud Syawaludin (Universitas Islam Negeri Ar-Raniry, 2020)
The purpose of this research is to describe and analyze the meaning and categorization of ukhuwah based on KH. Ahmad Shiddiq, namely Ukhuwwah Islamiyyah, Ukhuwwah Wathaniyyah, and Ukhuwwah Basyariyyah in the perspective of the Islamic elite of Pasuruan Regency. This research is using qualitative methodology with a phenomenological approach, unstructured and open interview data collection methods, moderate participatory observation, and documentation. Furthermore, the analysis and interpretation of data according to Miles and Huberman (1984) through the following steps: a). Data reduction, b). Display data, and c). Conclusion drawing/ verification. For data validity, using triangulation techniques or methods and triangulation of data or sources. This research is important to look for alternative narratives from phenomenon of the politicization of ukhuwah narrow one. This article is the first in discussing the various perspectives of Islamic religious elites in interpreting and implementing ukhuwah and formulating the concept of multicultural ukhuwah.